Supplier selection by using a fuzzy approach in just-in-time: A case study - Guneri, A. F.; Kuzu, A. (TAYLOR & FRANCIS LTD, 2009)
Supplier selection has received extensive attention in the just-in-time approach. Supplier selection and evolution are decisions of strategic importance to companies. Thus, supplier performance evaluation is very important in choosing the right supplier for the right product. In this paper, a method for supplier selection using fuzzy logic was performed. Fuzzy logic enables us to emulate the human reasoning process and make decisions based on imprecise data. The method is based on calculating a fuzzy suitability index for the efficient vendor alternatives, and then ranking the fuzzy indices to select the best supplier alternatives.
Keywords: just-in-time; fuzzy sets; decision-making/process; supplier selection; fuzzy suitability index (FSI); DECISION-SUPPORT-SYSTEM; VENDOR SELECTION; CHAIN MANAGEMENT; PERFORMANCE; CRITERIA; BUYER; MODEL; PREFERENCES; DESIGN; FIRMS; Computer Science; Engineering; Operations Research & Management Science